SYNTHESIS AND CHARACTERIZATION OF Zn1-x-yCdxLiyOÎ´ SOLID SOLUTION - Kamruzzaman, M.; S. Karal, M. A.; R. Khan, M. K.; Rahman, M. M.; Shahjahan, M.; M. Chowdhury, M. G. (The Nucleus, 2020)
Zn1-x-yCdxLiyOÎ´ (x=0.30; y=0.05, 0.10, 0.15, 0.20 and Î´= 0.975, 0.95, 0.925, 0.90) samples have been prepared by conventional solid state reaction method and studied their electrical, magnetic and structural properties. The dc electrical resistivity measurement shows that all samples are highly resistive ( 106 ohm-cm) upto a transition temperature (Tt), above which resistivity falls drastically that reveals the samples are semiconducting in nature and Tt decreases with increase of Li. The activation energies vary from (0.74-0.51) eV depending on doping concentrations, i.e. the activation energy is lower for higher concentration of Li in the solution. Magnetic mass susceptibility measurement shows negative sign that indicate the samples are diamagnetic. From XRD analysis, there exist two phases one is hexagonal ZnO and another is cubic CdO which suggests the formation of superlattice structure of the system. Crystallite size at planes (100), (002), (101), (102), (110), (103), (200), (112) and (111), (200), (220) for ZnO and CdO ranges from 20 to 50 nm and for Li ranges from 27 to 40 nm.